2017
DOI: 10.1002/cam4.1017
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐pocket costs and burden among rural breast cancer survivors

Abstract: Little is known about out‐of‐pocket (OOP) costs incurred for medical and health needs by rural breast cancer survivors and what factors may be associated with higher OOP costs and the associated economic burden. Data were examined for 432 survivors participating in the Rural Breast Cancer Survivor Intervention trial. OOP costs were collected using the Work and Finances Inventory survey at baseline and four assessments every 3 months. Mean and median OOP costs and burden (percent of monthly income spent on OOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 42 publications
(80 reference statements)
3
56
2
Order By: Relevance
“…Table summarizes the costs of adult cancer survivors from household survey‐based studies . Guy et al reported annual costs to all payers of $17,170 for recently diagnosed survivors and considerably lower costs for longer term survivors, although these were still higher than the costs among those without a history of cancer (Table ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table summarizes the costs of adult cancer survivors from household survey‐based studies . Guy et al reported annual costs to all payers of $17,170 for recently diagnosed survivors and considerably lower costs for longer term survivors, although these were still higher than the costs among those without a history of cancer (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Costs of medical care, including transportation costs, ranged from $129 to $149 per month over 1 year . Survivors also reported costs of counseling and health maintenance ranging from $88 to $167 per month, costs of side‐effect management ranging from $38 to $59 per month, and costs for home maintenance ranging from $138 to $186 …”
Section: Resultsmentioning
confidence: 99%
“…). Financial hardship, measured with 9 Work and Finances Inventory items such as filing for bankruptcy or losing savings due to cancer, was the number of these items experienced during the previous 6 months. Challenges in accessing care were assessed with questions adapted from the Medical Expenditure Panel Survey to determine whether respondents were unable to or were delayed in obtaining medical care, tests, treatments, or prescription medications within the previous 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to a deeper understanding of the costs that induce financial toxicity, identifying high‐risk patients is important (Carrera et al, ). Medical and non‐medical out‐of‐pocket costs have been found to be higher for patients with, for example, younger age, higher household income and longer distance from treatment centres (Baili et al, ; Davidoff et al, ; Newton et al, ; Pisu, Azuero, Benz, McNees, & Meneses, ; Valtorta & Hanratty, ). Furthermore, studies have found that low socioeconomic status is a risk factor for unemployment after a cancer diagnosis; for women, a cancer diagnosis results in a higher risk of unemployment, but mainly male cancer patients seem to be affected by a total decline in family income (Torp, Nielsen, Fosså, Gudbergsson, & Dahl, ; Zajacova et al, ).…”
Section: Introductionmentioning
confidence: 99%